Early cutaneous leishmaniasis in a newborn baby. - Hocar, O.; Akhdari, N.; Moutaj, R.; Amal, S. (European Journal of Pediatric Dermatology, 2012)
Cutaneous leishmaniasis can arise at any age but neonatal cutaneous leishmaniasis is exceptional. We report a case of early cutaneous leishmaniasis appeared since birth in a boy treated successfully with clarithromycin. The case here reported was exceptional for its very early onset, which did not suggest initially the diagnosis of leishmaniasis, and also for the lack of spontaneous regression after 7 months, that led us to perform clarithromycin therapy. The clinical studies using macrolides for the treatment of cutaneous leishmaniasis were also reviewed.